2002
DOI: 10.4049/jimmunol.168.3.1212
|View full text |Cite
|
Sign up to set email alerts
|

CpG Are Efficient Adjuvants for Specific CTL Induction Against Tumor Antigen-Derived Peptide

Abstract: The identification of CTL-defined tumor-associated Ags has allowed the development of new strategies for cancer immunotherapy. To potentiate the CTL responses, peptide-based vaccines require the coadministration of adjuvants. Because oligodeoxynucleotides (ODN) containing CpG motifs are strong immunostimulators, we analyzed the ability of CpG ODN to act as adjuvant of the CTL response against tumor-derived synthetic peptide in the absence or presence of IFA. Mice transgenic for a chimeric MHC class I molecule … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
94
2
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 134 publications
(105 citation statements)
references
References 44 publications
8
94
2
1
Order By: Relevance
“…Although some studies have showed induction of MUC1-specific antibodies in animal models and cancer patients [Reviewed in 10], our studies demonstrating the induction of CTL responses corroborate numerous reports in which CpG-ODN alone [33,37,48,49] or in combination with GM-CSF [24] were used as biologic adjuvants in peptide vaccines. A likely explanation of our results is that MHC class I-restricted MUC1 peptides which stimulate CD8 + T cells are acting in concert with CpG-ODN and GM-CSF in the vaccine cocktail to promote strong T H1 type responses resulting in the generation of efficient CTL anti-tumor responses [24,33,37,48,50]. In addition, inclusion of CpG-ODN in the vaccination cocktail in our study did not cause destruction of the lymphoid follicles or prevent isotype switching in treated mice (data not shown) as was reported by Heikenwalder, et al [51].…”
Section: Discussionsupporting
confidence: 88%
“…Although some studies have showed induction of MUC1-specific antibodies in animal models and cancer patients [Reviewed in 10], our studies demonstrating the induction of CTL responses corroborate numerous reports in which CpG-ODN alone [33,37,48,49] or in combination with GM-CSF [24] were used as biologic adjuvants in peptide vaccines. A likely explanation of our results is that MHC class I-restricted MUC1 peptides which stimulate CD8 + T cells are acting in concert with CpG-ODN and GM-CSF in the vaccine cocktail to promote strong T H1 type responses resulting in the generation of efficient CTL anti-tumor responses [24,33,37,48,50]. In addition, inclusion of CpG-ODN in the vaccination cocktail in our study did not cause destruction of the lymphoid follicles or prevent isotype switching in treated mice (data not shown) as was reported by Heikenwalder, et al [51].…”
Section: Discussionsupporting
confidence: 88%
“…The role of immune modulation of unmethylated CpG in governing the immune response has been described both in rodents and in nonhuman primates. 48,49 Thus, as a number of CpG has been introduced into the synthetic cDNA of CEA, these may also contribute to the enhanced immunogenic properties of the CEA expressing vectors.…”
Section: Discussionmentioning
confidence: 99%
“…Synthetic DNA made of a stabilizing phosphorothioate backbone and containing at least one CpG motif can mimic bacterial DNA [10]. It can be added to vaccine formulations (even those already containing some other PAMP) and allow or enhance immune responses in mice and other animals (for example, apes [11][12][13]) in the context of vaccines based on DNA, peptides [14,15], proteins [16][17][18][19], virus-like particles [20], attenuated viruses [21] or inactivated bacteria [22], whether parenteral [23] or mucosal delivery of the vaccine is used [12,[24][25][26]. Moreover, synthetic immunostimulating DNA injected alone into tumors can prime a curative anti-tumor immune response by signaling danger in this otherwise "healthy" pathogenic tissue [27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%